PHYSICAL CONFLICT ANALYSIS IN THE NOVEL “INTO THIN AIR” BY JON KRAKAUER - Chandra Ivan; Agita Violy (STIBA IEC JAKARTA, 2021)
This research aims to enlarge knowledge and understanding the element of literature, especially in conflict element. It is very important to know about conflict in literature because the readers can understand to response every condition through representation conflict in this novel. The writer focuses on conflict rising up from the beginning to the end of the story. There are so many people in the groups that want to climb Everest. And of course, in an expedition, especially in a dangerous mountain like Everest has so many conflicts. This research is descriptive qualitative research. This thesis uses physical conflict analysis and also applies psychological aspect to analyze the main characters’ characteristics when struggle a force of nature such as the rogue storm that caused disaster. The story reminds the readers of a journey of life. It reminds us that everybody do not be arrogance and must ready to face everything that will happen in the future. It also remind us to being trust and loyalty among teammate.